Intrauterine platelet rich plasma versus injection G-CSF for treatment of thin endometrium in infertility - Vora, Amishi Vijay; Nadkarni, Purnima K.; Garasia, Jigna; Nadkarni, Aditi; Singh, Pooja Nadkarni; Nadkarni, Vaibhav K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: For success in IVF treatment, it is essential that the patient has a responsive endometrium together with many other factors. Inspite of numerous treatments available today for growth of endometrium, there is lack of any ideal drug or protocol for increasing endometrial thickness. The study is an attempt to evaluate the role of two drugs for increasing endometrial growth before embryos transfers. Methods: This study is a retrospective cohort study including 50 patients with previously diagnosed as thin endometrium patients who may or may not have failed previous cycles of IVF. Patients were randomly divided into two groups. First group-Group A (n=25) are patients randomly selected to undergo intrauterine PRP instillation for increase in endometrial thickness before embryo transfer. Second group-Group B (n=25) are randomly selected from a retrospective cohort of thin endometrium to take injection GCSF as intrauterine infusion (total dose 300mcg) on day of trigger or day 11 of cycle followed by 60 units subcutaneously after embryo transfer. The difference in endometrial thickness during transfer and the pregnancy outcomes were compared. Results: Injection GCSF was found to be more effective than intrauterine PRP in improving endometrial thickness in patients with thin endometrium with a p-value of <0.0001. It was found that the chemical and clinical pregnancy rates were comparable as the p values were 0.77 and 0.37 respectively and hence statistically not significant. Although patients given injection GCSF had a slightly higher clinical pregnancy rate (44%) as compared to patients given intrauterine PRP which was 28%. All other variables were comparable. Conclusions: In the study it was proven that injection GCSF, is more effective for the treatment of thin endometrium patients as compared to intrauterine PRP infusion. Though the clinical and chemical pregnancy rates were comparable, a higher percentage of women were clinically pregnant in the group given injection GCSF. Intrauterine PRP can also be a good alternative for thin endometrium. More studies and RCTS are needed for comparison to prove the effectiveness of these drugs for treatment of thin endometrium.